2018
DOI: 10.4300/jgme-d-18-00244.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Handoffs: Implementing a Training Program for Incoming Internal Medicine Residents

Abstract: Background The Accreditation Council for Graduate Medical Education Clinical Learning Environment Review program requires residents to receive training in handoffs, but there is limited information on best practices in implementing handoff training.Objective We hypothesized that a bundled, standardized approach to handoffs during intern orientation would increase trainee comfort, confidence, and knowledge.Methods All incoming internal medicine interns participated in a Care Transitions workshop during orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…The ACGME Clinical Learning Environment Review outlines the need for education in care transitions and standardized handoffs in resident education (ACGME, 2018). Studies support the utilization of standardized handoff training and formats as these interventions have been shown to increase trainee comfort and decrease medical errors (Lescinskas, Stewart and Shah, 2018;Starmer et al, 2014).…”
Section: Standardize Socially Distanced Sign-outsmentioning
confidence: 99%
“…The ACGME Clinical Learning Environment Review outlines the need for education in care transitions and standardized handoffs in resident education (ACGME, 2018). Studies support the utilization of standardized handoff training and formats as these interventions have been shown to increase trainee comfort and decrease medical errors (Lescinskas, Stewart and Shah, 2018;Starmer et al, 2014).…”
Section: Standardize Socially Distanced Sign-outsmentioning
confidence: 99%
“…Recent reports have indicated that engaging students in vocation-oriented internships and placements are an effective way to enhance their professional skills and employability. Internship experiences help students increase their opportunities for different positions after they graduate from university, regardless of their university majors, but particularly if they graduate with non-vocation-oriented degrees [31,32]. Graduates with internship experience are more likely to be chosen for interviews than those without such experience [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have confirmed the importance of providing residents with structured training about TOC mnemonic use via interventions such as bootcamps, didactic sessions, and/or simulated learning experiences, but little research is available on TOC postintervention reinforcement via direct observation of actual patient encounters. 12,13 Our expectation was that use of a direct observation instrument, Transitions of Care-Clinical Evaluation Exercise (TOC-CEX), by faculty as both a monitoring and education tool would increase awareness and adoption of TOCs as a practice habit and contribute to culture change in the clinical learning environment.…”
Section: Introductionmentioning
confidence: 99%